2011
DOI: 10.1039/c1ob05816a
|View full text |Cite
|
Sign up to set email alerts
|

Control of chemoselectivity in Dieckmann ring closures leading to tetramic acids

Abstract: An efficient strategy for the control of the chemoselectivity in Dieckmann ring closures leading to tetramic acids derived from serine and α-methyl serine is reported, and this provides pathways to diversely substituted systems from a common starting material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…a Cyclization under standard conditions (reflux in presence of KO t ‐Bu) successfully gave the desired tetramates 7a–e, g in very good yield (Table ) and as single diastereomers, with the ring stereochemistry again readily established by NOE analysis (Figure ). b Noteworthy was that in these systems, reaction proceeded by initial epimerization of 6a–g to epi ‐6a–g followed by ring closure from the malonyl α‐carbon onto the C(4) ester of the thiazolidine ring to give products 7a–e, g (Scheme 3); this had been earlier found to be minor pathway in the serine and threonine systems leading to tetramates 3a, b (Scheme 1) , and we attribute this difference both to the smaller aromatic substituent on the thiazolidine ring and to the larger sulphur atom, which makes the alternative C(4) enolate attack onto the terminal ethyl ester less sterically favourable. This is borne out by the fact that in the ring closure of thiazolidine 6 (R= t ‐Bu), product 7 (R= t ‐Bu) was obtained only as the minor product, with product 3c (X=S, R=H) formed as the major one, as has been observed in the oxazolidine series .…”
Section: Yields and Cheminformatic Data For Products In Schemementioning
confidence: 83%
See 1 more Smart Citation
“…a Cyclization under standard conditions (reflux in presence of KO t ‐Bu) successfully gave the desired tetramates 7a–e, g in very good yield (Table ) and as single diastereomers, with the ring stereochemistry again readily established by NOE analysis (Figure ). b Noteworthy was that in these systems, reaction proceeded by initial epimerization of 6a–g to epi ‐6a–g followed by ring closure from the malonyl α‐carbon onto the C(4) ester of the thiazolidine ring to give products 7a–e, g (Scheme 3); this had been earlier found to be minor pathway in the serine and threonine systems leading to tetramates 3a, b (Scheme 1) , and we attribute this difference both to the smaller aromatic substituent on the thiazolidine ring and to the larger sulphur atom, which makes the alternative C(4) enolate attack onto the terminal ethyl ester less sterically favourable. This is borne out by the fact that in the ring closure of thiazolidine 6 (R= t ‐Bu), product 7 (R= t ‐Bu) was obtained only as the minor product, with product 3c (X=S, R=H) formed as the major one, as has been observed in the oxazolidine series .…”
Section: Yields and Cheminformatic Data For Products In Schemementioning
confidence: 83%
“…b Noteworthy was that in these systems, reaction proceeded by initial epimerization of 6a-g to epi-6a-g followed by ring closure from the malonyl a-carbon onto the C(4) ester of the thiazolidine ring to give products 7a-e, g (Scheme 3); this had been earlier found to be minor pathway in the serine and threonine systems leading to tetramates 3a, b (Scheme 1) (11), and we attribute this difference both to the smaller aromatic substituent on the thiazolidine ring and to the larger sulphur atom, which makes the alternative C(4) enolate attack onto the terminal ethyl ester less sterically favourable. This is borne out by the fact that in the ring closure of thiazolidine 6 (R=t-Bu), product 7 (R=t-Bu) was obtained only as the minor product, with product 3c (X=S, R=H) formed as the major one, as has been observed in the oxazolidine series (11). Cheminformatic analysis (Table 1) indicated that several of these compounds were indeed significantly more polar than the t-butyl analogue 7 (R=t-Bu) (ClogP = 1.97, Polar Surface Area [PSA] = 63.7, %PSA = 15.0), but all compounds have very similar molecular volumes in the range of 235-280 A 3 .…”
mentioning
confidence: 87%
“…3 Interestingly, methodology for the general preparation of β-tricarbonyl systems is scarce, 9 and we have recently reported methodology providing access to highly substituted 3-acyltetramates, which relies upon Dieckmann cyclisation of templates 2 derived from serine, 10 threonine 11 or cysteine, 12 the chemoselectivity of which can be controlled by judicious use of reaction conditions and substituents to give products 3 and/or 4 (Scheme 1). 13 Moreover, we have established a reliable approach for the introduction of diverse 3-acyl groups into either of 3 or 4, 14 and this permits rapid generation of chemical diversity around the core tetramate scaffold. In some cases, these compounds possess potent antibacterial activity, 15,16 even though the core tetramate system itself is generally devoid of such activity.…”
mentioning
confidence: 99%
“…Due to steric effects, the N-acylation of the trans pseudoproline (S,S)-9 is strongly disfavored and only the cis (R,S)-9 pseudoproline reacts to afford exclusively the dipeptide bearing the cis (R,S)-oxazolidine. 57,58 It is important to note that no epimerization of the C δ occurs once the pseudoprolines are N-acylated.…”
Section: Scheme 4 C-terminal Coupling Reaction Of the Pseudoproline mentioning
confidence: 99%